PRELIMINARY STUDY ON ANTIFUNGAL ACTIVITY OF NEOLAMARCKIA MACROPHYLLA LEAVES EXTRACT - Fazia, Mohamad Sinang; Michelle, Ngassy Mering; Ho Wei, Seng (2021)
The genus Neolamarckia includes two species which are N. macrophylla and N. cadamba. Many research have been done on various aspect of N. cadamba including the antimicrobial and the phytochemical compounds in the extract of different part of the tree (Qureshi et al., 2021; Islam et al., 2015). In contrary with N. cadamba, there are very limited research study on N. macrophylla. The aims of this research were to extract the antifungal properties of N. macrophylla leaf using aqueous and methanol extraction followed by the evaluation of antifungal activity of the leaf extracts against Aspergillus flavus, Aspergillus niger and Fusarium solani. Extracts of different concentration (12.5 mg/mL, 25 mg/mL, 50 mg/mL and 100 mg/mL) were spread on the potato dextrose agar to evaluate the fungi growth using the poisoned food technique. The results were compared with the normal growth of the fungi in potato dextrose agar. The results on fungi growth showed inconsistency of inhibitory effect on the test fungi exhibiting inhibition percentage within the range of 4-80%. Further improvement on the evaluation of antifungal activity needed in future research to obtained consistent results as to ensure validity of the data.